Dental caries experience in children with congenital heart disease: a case-control study - C. STECKSÉN-BLICKS, A. RYDBERG, L. NYMAN, S. ASPLUND, & C. SVANBERG (Paediatric Dentistry, 2004)
To compare the dental health of a group of children with complex congenital heart disease with that of age and gender matched healthy controls.